Salvatore Giuliano - Rosi, Francesco 1922-2015; Wolff, Frank; Randone, Salvo 1906-1991; Zardi, Federico; Cammarata, Pietro; Teti, Giuseppe (Lux Film Vides Galatea, 2005)
A documentary-style drama chronicling the rise and fall of the title character, a real-life Mob chieftain who rose to prominence in post-WWII Sicily.
Sceneggiatura: Suso Cecchi d'Amico, Enzo Provenzale, Francesco Rosi, Franco Solinas, fotografia: Gianni di Venanzo, musica: Piero Piccioni, costumi: Marilù Carteny
Bildformat 1.85:1
Original: Italien 1962
Keywords: Giuliano, Salvatore <1922-1950>; Assassinio - Dramma; Assassination -- Drama; Criminal behavior -- Drama; Film; DVD-Video